The role of multiple materials to enrich contemporary mural painting (Al-Academy, 2025)
The research presents a study on multiple materials and various media in enriching contemporary mural painting in a visual space that allows the formation of a perception enriches the aesthetic vision in the artistic work. Through the diversity of media and multiple materials and the intersection of genres within an atmosphere characterized by unity, by tracing the beginning of the emergence of the technique of combining more than one material in mural painting During ancient civilizations, and the transformation that occurred in modem manufactured and pre- processed raw materials in contemporary works, the study has four chapters, the first is the general framework of the research problem, the second is theoretical framework about the various techniques and materials in enriching the field of mural painting and how to form them within the work unit, the third deals with some mural works in terms of the multiplicity of materials in them and the extent of the influence of the material in enriching it functionally and aesthetically, fourth results and sources.